Diplomatic Dynamics of International Treaty Negotiations - Dong, Tianhang; Zeng, Robin; Ma, Timmy (The PUMP Journal of Undergraduate Research, 2019)
The negotiation process of international treaties is heavily influenced by socioeconomic factors. In this paper, we aim to answer the question of how to quantify the influential factors among countries. We do so by categorizing them into different interest groups based on their attitudes towards the treaty as well as their socioeconomic statuses and modeling the movement of countries between these interest groups. This model is based on an epidemiological approach to quantifying influence. Through our research, we discovered two equilibrium points, which reveal the conditions under which all countries would either support or oppose a treaty. We also ran simulations under several hypothetical scenarios under which equilibria would occur, demonstrating the practical applications of our model. We further analyze the model's real life application and the influence of certain parameters through two case studies: the first is on the Basel Convention's negotiation process and the second is on the spread of carbon pricing.